Exploring 'Chinese' art film aesthetic influences on independent Chinese Malaysian filmmakers / Gaik Cheng Khoo - Gaik, Cheng Khoo (UPENA, 2008)
Independent Chinese Malaysian films have been associated with the work of Tsai Ming Liang, Hou Hsiao Hsien, Wong Kar Wai and others. James Lee, Tan Chui Mui, Ho Yuhang, Khoo Eng Yow, Woo Ming Jin and now Liew Seng Tat and Brando all favour focusing on the everyday life of marginal or working class characters, minimal dialogue and subtle storytelling. Lately, the films may be said to have more in common with the work of the 6th Generation mainland Chinese filmmakers who also shoot on digital. This paper seeks polemically to explore whether there is indeed such a 'Chinese film aesthetic,' tracing its influences through Italian social realism and other trends through film history to more current trends. Aside from favouring the works and styles of specific directors, are these filmmakers also influenced by the desires of film festival programmers and film curators looking for 'difference,' as well as the commodification of the art film market overseas? For example, Liew, who counts Stephen Chow (of Kungfu Hustle fame) among his favourite directors, for his debut feature Flower In The Pocket (2007), chooses an aesthetic quite opposed to that of Chow, one closer to home and to his Malaysian Independent Film (MIF) collaborators. What is going on? While the focus on the everyday and the mundane is realistic given the low-budgets they are working with, that still leaves aside the question of filmmaking style and aesthetics. How much of it is derivative of external influences, whether one is drawn to the style of art cinema, or one is rejecting classic Hollywood narrative styles? And how much of it is reflective of the filmmaker's personality, individual circumstance and habitus?